Masks and the question of identity: an examination of multiple identities in Smith’s Ginette (1980) ,Charter’s Crossing the boundary fence(1988), Partridge’s To breathe and wait(1986). - Bususu, Lenah-lisa (Midlands State University, 2014)
This research examines the representation of multiple identities in literary texts through an analysis of Crossing the Boundary Fence by Patricia Charter (1988), To Breathe and Wait by Nancy Partridge (1986) and Ginette by Sylvia S Bond (1980). Multiple identities manifest themselves in everyday life as we know it. The question of how identity changes, at what point and with what effect, have long been overlooked. In prose writing, the author is oftentimes unaware of the voice or voices given to their characters through language use. These voices act as masks worn during a particular conversation with which a literary character is able to reflect and refract a particular identity. The identities transcend, antagonise and work together to produce a desired, conversational outcome and this can be referred to as the desired mask. Texts written during the liberation struggle are ideal in producing evidence of these masks across age, culture, race and ethnic groups. The texts help bring out a lot of conflicting situations and the language that is evident of multiplicity in human identity.